Identification of a response regulator involved in surface attachment, cell–cell aggregation, exopolysaccharide production and virulence in the plant pathogen Xylella fastidiosa. (27th November 2012) - Voegel, Tanja M.; Doddapaneni, Harshavardhan; Cheng, Davis W.; Lin, Hong; Stenger, Drake C.; Kirkpatrick, Bruce C.; Roper, M. Caroline
Summary Xylella fastidiosa, the causal agent of Pierce's disease of grapevine, possesses several two‐component signal transduction systems that allow the bacterium to sense and respond to changes in its environment. Signals are perceived by sensor kinases that autophosphorylate and transfer the phosphate to response regulators (RRs), which direct an output response, usually by acting as transcriptional regulators. In the X. fastidiosa genome, 19 RRs were found. A site‐directed knockout mutant in one unusual RR, designated XhpT, composed of a receiver domain and a histidine phosphotransferase output domain, was constructed. The resulting mutant strain was analysed for changes in phenotypic traits related to biofilm formation and gene expression using microarray analysis. We found that the xhpT mutant was altered in surface attachment, cell–cell aggregation, exopolysaccharide (EPS) production and virulence in grapevine. In addition, this mutant had an altered transcriptional profile when compared with wild‐type X. fastidiosa in genes for several biofilm‐related traits, such as EPS production and haemagglutinin adhesins.